His shoes were far too tight - Lear, Edward, 1812-1888 (Chronicle Books, 2011)
Come inside this book and meet the Pobble with his chilly feet, the Owl and the Pussycat, a Sieve to sail away and back, a hive of silvery bees. Come inside this book and find poetry to feed your mind.